Parental asthma and risk of autism spectrum disorder in offspring: A population and family‐based case‐control study - Gong, Tong; Lundholm, Cecilia; Rejnö, Gustaf; Bölte, Sven; Larsson, Henrik; D'Onofrio, Brian M.; Lichtenstein, Paul; Almqvist, Catarina (Clinical and experimental allergy, 2019)
Summary Background Associations between parental asthma and prenatal exposure to asthma medications with offspring autism spectrum disorder (ASD) have been reported. However, the associations might be confounded by unmeasured (genetic and shared environmental) familial factors. Objective We investigated the association between (a) maternal/paternal asthma and offspring ASD, and (b) prenatal exposures to β2‐agonists, other asthma medications and offspring ASD using cases and controls selected from the population as well as biological relatives with different degrees of relatedness. Methods We included all children (N = 1 579 263) born in Sweden 1992‐2007. A nested case‐control design was used to compare 22 894 ASD cases identified from the National Patient Register to (a) 228 940 age‐, county‐ and sex‐matched controls randomly selected from the population, (b) their eligible full‐siblings (n = 1267), (c) half‐siblings (n = 1323), (d) full‐cousins (n = 11 477) and (e) half‐cousins (n = 3337). Conditional logistic regression was used to estimate the odds ratios (OR) and 95% confidence intervals (CI) for ASD in children differentially exposed to parental asthma or prenatal asthma medications. Results Maternal asthma was associated with increased risk of offspring ASD (OR 1.43, 95% CI 1.38‐1.49); there was a weaker association for paternal asthma (OR 1.17, 95% CI 1.11‐1.23). The risk of offspring ASD in mothers with asthma showed similar estimates when adjusting for shared familial factors among paternal half‐siblings (OR 1.20, 95% CI 0.80‐1.81), full‐cousins (OR 1.28, 95% CI 1.16‐1.41) and half‐cousins (OR 1.30, 95% CI 1.10‐1.54), albeit with wider confidence intervals. Prenatal exposure to asthma medications among subjects whose mothers had asthma was not associated with subsequent ASD. Conclusions and Clinical Relevance In this large observational study, parental asthma was associated with slightly elevated risk of ASD in offspring. More specifically, the increased risk by maternal asthma did not seem to be confounded by familial factors. There was no evidence of an association between asthma medications during pregnancy and offspring ASD.